2018
DOI: 10.1111/1752-1688.12681
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow Alteration from Impervious Cover: Are All Watersheds Created Equal?

Abstract: Very small amounts of impervious cover can impact streamflows. In the Potomac basin, for example, significant streamflow alteration associated with watershed impervious cover >0.5%–2.0% have been found. Since these impacts were found with considerably lower amounts of impervious cover than previously documented in the literature, typically 10%–20%, this study evaluated whether certain watershed characteristics (e.g., watershed area, karst geology, precipitation, soil characteristics, physiographic province, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…For each watershed, we calculated various hydrologic metrics related to flow magnitude or flashiness (Table 2). We used the Indicators of Hydrologic Alteration software (The Nature Conservancy, 2009) to generate metrics based on daily flow data, since this is a software that has been commonly used to evaluate flow regime and ecological flow metrics (e.g., McDaniel & O'Donnell, 2019;Moltz et al, 2018;Schoonover et al, 2006;The Nature Conservancy, 2006). Both Indicators of Hydrologic Alteration and another increasingly used similar software-the USGS's EflowStats package for R-only calculate metrics for daily flow data (US Geological Survey, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each watershed, we calculated various hydrologic metrics related to flow magnitude or flashiness (Table 2). We used the Indicators of Hydrologic Alteration software (The Nature Conservancy, 2009) to generate metrics based on daily flow data, since this is a software that has been commonly used to evaluate flow regime and ecological flow metrics (e.g., McDaniel & O'Donnell, 2019;Moltz et al, 2018;Schoonover et al, 2006;The Nature Conservancy, 2006). Both Indicators of Hydrologic Alteration and another increasingly used similar software-the USGS's EflowStats package for R-only calculate metrics for daily flow data (US Geological Survey, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of watersheds in major metropolitan areas across the United States found that lower slopes and higher soil permeability in urban watersheds reduced high flow events and flashiness but increased high flow durations (Hopkins et al, 2015). Modeling scenarios in the Potomac River basin found strong interactions between presence of karst geology, slope, precipitation, and watershed area with imperviousness impacts on streamflow regimes (Moltz et al, 2018); for example, small, flatter watersheds were most susceptible to increases in flashiness due to imperviousness, presumably because more sloped watersheds are already flashier. In our study, we observed interactions between precipitation and mean annual area-weighted flowrate with imperviousness; for example, decreased flashiness and zero-flow days and increased POTs were observed with higher imperviousness and higher precipitation or average flowrates (Tables 3 and 4).…”
Section: Water Resources Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is a reduced negative impact on water and environmental resources from human activities. The impacts of urbanization on stream water quantity and quality has been well documented in the literature [4,9,[102][103][104].…”
Section: Case Study: Placemakingmentioning
confidence: 99%
“…The impacts of land management on the quality and quantity of sustainable water resources are well documented in the literature [2][3][4][5]. Each land use type (e.g., urban, agriculture, and forest) has specific, scale-dependent effects [6,7] on surface-and ground-water ecology, availability, demands, and quality [8][9][10][11][12][13]. The successful management of one (land or water resources) should by default involve the consideration of the other [14]; however, this is rarely the case.…”
Section: Introductionmentioning
confidence: 99%